Storyteller Sh.V. Boktaev and his repertory - Mandzhieva, Bayrta B. (The New Research of Tuva, 2013)
Article reviews on of the best known Kalmyk storytellers Shan Vasillievich Boktaev who has left plenteous heritage of oral folk arts.
Keywords: Sh.V.Boktaev; storyteller; folklore; Kalmyks